Thermoelectric Module Application for Deep Freezing - Singh, Suraj (My University, 2019)
With the increasing demand of having a lower temperature in the freezer than the existing, home appliance companies are doing continuous research to come up with a product that has the capability of achieving such a desired lower temperature, say -50⁰C. Such a lower temperature is desired because the ice forming time of most of the commercial refrigerator is 90 min to 120 min and also due to the fact that few stuffs required to be stored at considerably lower temperature, whereas the existing capability of freezer in the refrigerator is -25⁰C. Also, due to continuous or periodic opening of freezer, the temperature drops with every opening and therefore, stabilisation of that temperature will again take some time. Therefore, if there would be a separate compartment or box in the freezer that can withstand such a desired lower temperature, then an isolated box in the freezer can be made which would be practically isolated from the rest of the freezer. By having a temperature of -50⁰C, the ice making time will be reduced to 30 min. Commercially available refrigerators with inbuilt ice-makers have the problem of its size and the space that it utilizes. Apart from that, an ice maker is capable of making ice only and nothing can be stored in an ice maker, whereas a deep freezer can store things apart from making ice. Also, extra amount of refrigerant is needed to be added to the system for the working of ice maker. The idea presented in this thesis is to make a separate zone in the freezer that has the capability of achieving a temperature of -50⁰C along with a temperature difference of 50 or more without using any refrigerant or traditional refrigeration cycle. To achieve this deep freezer temperature, thermoelectric or peltier modules are used and a prototype for deep freezer is fabricated. The heat load required to be handled for making ice in 30 min is calculated and correspondingly a module selection is carried out on the basis of such heat load. Performance analysis of the module is done and several modules were selected on the basis of such analysis. After choosing such modules, a series of experimentation was carried out to achieve the desired goal. Cascading of the module was done to save on cost and desired goal was achieved. At the end, future work is suggested to carry out the experimentation by placing the prototype of deep freezer within the freezer of a refrigerator.
Keywords: Deep freezer; Refrigerant; Thermoelectric or peltier module; Prototype; Cascading; Deep freezer temperature